Feasibility of Embung (basin retention) in Green Open Space Area over Institut Teknologi Sumatera (ITERA) - Tastaptyani Kurnia Nufutomo; Fitralia Elyza (Penerbit Kemala Indonesia, 2018)
ITERA has six potential embung (reservoir) as a habitat for fresh water flora and fauna, for place of learning and as water tourism. The function of embung (reservoir) is in accordance with ministry PUPR regulation No. 9/2015 is about using water resources, the embung can be utilized as rain retention basin, and aquaculture activity. Water quality in embung (reservoir) will decrease along with many anthropogenic activites that take place around the embung. This study aims to determine the feasibility of embung water quality and customized with ministry Environmental regulation of water quality management and water pollution control No. 82/2001. Embung (reservoir) in ITERA is belonging to the second class category of water quality management. The purpose of research was to analyze water quality parameters including temperature, phosphate, nitrate, BOD, Turbidity, pH, DO, TSS, and Coliform. There are three embung (reservoir) to be sampled on composite. Embung A is located near the highway, Embung B is located near the north entrace gate of ITERA and Embung C is located near LPPM ITERA building. The output of our research will be a source of data reference for follow up in the identification of water pollution and as a form of water quality management of the embungs.